Citra Ikemen dalam Cosplayer Crossdress Female to Male (F2M) di Komunitas Cosplay Bandung - Muhlisian, Asep Achmad; Setyono, Zalva Rona Santika (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2023)
This study examines Ikemen's image in female to male (F2M) Crossdresser Cosplayers in the Bandung Cosplay Community. The purpose of this study is to describe the image of ikemen in female to male (F2M) Crossdresser Cosplayers at the Bandung Cosplay Community and to describe female to male (F2M) Crossdresser Cosplayers when performing ikemen on stage. The method used is descriptive qualitative. Data collection uses the Library Study technique, collection through books, journals, and other supporting literature as reference material and Field Studies. The results of this study indicate that the image of ikemen in the female to male (F2M) Crossdresser Cosplayer in the Bandung Cosplay Community is a male figure depicted with a handsome face that they display through make up, attractive stature, tall and well-built, and charismatic